(untitled) (Revista INTEREDU11, 2021)
This article explores how the anti-racial discrimination logic has been installed and positioned as the only category in ethno-educational discourses and practices, leaving aside other areas of exclusion and segregation associated with class, territory and gender, among others. Through the analysis of critical, intercultural and intersectional curricula, other possibilities are proposed for the approach and understanding of the different variables that are interwoven in the complex systems of domination, oppression and exclusion. In this way, the study tends to redefine the theoretical and epistemological bases of Afro-Colombian ethno-education, generating ruptures with the classist, sexist and racialized colonial legacy that prevails today. The study reveals the absences and tensions that underlie the confrontation of traditional theories of the curriculum with those proposed by critical and intercultural curricula that construct dialogic scenarios based on the historical-social configurations of subjects and communities.